Multimorbidity and emergency department visits by a homeless population: a database study in specialist general practice - Bowen, Matthew (Br J Gen Pract, 2019)
BACKGROUND: Estimating healthcare needs of the homeless is associated with challenges in identifying the eligible population. AIM: To explore the demographic characteristics, disease prevalence, multimorbidity, and emergency department visits of the homeless population. DESIGN AND SETTING: EMIS electronic database of patient medical records and Quality and Outcomes Framework (QOF) data of all 928 patients registered with a major specialist homeless primary healthcare centre based in the West Midlands in England, from the period of October 2016 to 11 October 2017. METHOD: Prevalence data on 21 health conditions, multimorbidity, and visits to emergency departments were explored and compared with the general population datasets. RESULTS: Most homeless people identified were male (89.5%), with a mean age of 38.3 (SD = 11.5) years, and of white British origin (22.1%). Prevalence of substance (13.5%) and alcohol dependence (21.3%), hepatitis C (6.3%), and multimorbidity (21.3%) were markedly higher than in the general population. A third (32.5%) had visited the emergency department in the preceding 12 months. Emergency department visits were associated with a patient history of substance (odds ratio [OR] = 2.69) and alcohol dependence (OR = 3.14). CONCLUSION: A high prevalence of substance and alcohol dependence, and hepatitis C, exists among the homeless population. Their emergency department visit rate is 60 times that of the general population and the extent of multimorbidity, despite their lower mean age, is comparable with that of 60–69-year-olds in the general population. Because of multimorbidity, homeless people are at risk of fragmentation of care. Diversification of services under one roof, preventive services, and multidisciplinary care are imperative.